2019
DOI: 10.1111/evj.13065
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided injection of the cranial tibial artery for stem cell administration in horses

Abstract: Summary Background A technique for intra‐arterial injection of mesenchymal stem cells (MSC) has been established for front limbs with the use of the median artery. This approach has been proposed for treatment of soft tissue injuries of the equine distal limb. A technique has not been validated yet for hindlimb injection. Objectives To assess the feasibility of injection of the cranial tibial artery in horses, and to evaluate the distribution and persistence of MSC after injection. Study design In vivo experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…We did not compare the diagnostic accuracy of CT, which is beyond the scope of the current study. One of the advantages of this CT unit is that the limb can be positioned on a partially non-weightbearing limb and thus Recently, ultrasound-guided injection of median and cranial tibial arteries in standing sedated horses has been described (Spriet et al 2015;Torrent et al 2019). We did not attempt to perform intra-arterial enhanced contrast CT since extra equipment, such as saline chaser, is required for providing a constant infusion of the contrast agent, which may not be practicable in standing horses.…”
Section: Discussionmentioning
confidence: 99%
“…We did not compare the diagnostic accuracy of CT, which is beyond the scope of the current study. One of the advantages of this CT unit is that the limb can be positioned on a partially non-weightbearing limb and thus Recently, ultrasound-guided injection of median and cranial tibial arteries in standing sedated horses has been described (Spriet et al 2015;Torrent et al 2019). We did not attempt to perform intra-arterial enhanced contrast CT since extra equipment, such as saline chaser, is required for providing a constant infusion of the contrast agent, which may not be practicable in standing horses.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, to treat tendon lesions, MSCs were exclusively applied intralesionally. More recently, it was shown that autologous MSCs applied intravenously, or intra-arterially, may also elicit a beneficial effect in the treatment of tendinopathies when compared with anti-inflammatory drugs [30,[100][101][102].…”
Section: Regenerative Therapiesmentioning
confidence: 99%
“…Sole et al (145) observed arterial thrombosis in horses when the intraarterial application of allogeneic BMMSC was performed via IA regional limb perfusion. Interestingly, the complication of thrombosis was not detected when performing IA injection without using a tourniquet, indicating that a thrombosis is a consequence of blood stasis and not the MSC application (147). Similarly, IA injection of MSC was proven feasible with allogeneic equine BMMSC injected into the cranial tibial artery in horses, also without a tourniquet (148).…”
Section: Msc Homingmentioning
confidence: 99%